The importance of conscientiousness in the telemarketing industry - B. Gaertner; L. Lambson; M. Mbuyu; E. Botha (South African Journal of Business Management, 2015)
Researchers have long pondered the personality type-performance relationship. However, in the sales industry and especially in telemarketing, findings have been contradictory with regards to which personality trait best contributes to performance. The telemarketing industry is a rapidly growing industry, but is typically marred with high staff turnover and low levels of performance. An improved understanding of the factors that contribute towards performance in this industry is a key mandate of management. Personality-type has been shown to be a key driver of performance in the sales industry. However, it is unclear whether the personality types touted in typical sales positions (for example extroversion) are suited for the telemarketing environment. South Africa is one of the top emerging call centre locations in the world and as such the purpose of this study was to determine which personality type best contributes towards performance in the South African telemarketing industry. A census was conducted on telesales personnel in a large telemarketing organisation and the five-factor model was used to test employees' personality types. Contrary to current research, which suggests that extraversion is the five-factor trait best suited to salespeople, this study found that conscientiousness was the only personality trait that influenced sales performance in the call centre context.
Keywords: 650